Choosing the Right Lens – When Round Must Become Square: Five factors to consider when choosing the right lens for a camera or imaging system. Issue 5 (11th December 2017) - Simon, Stephanie
Abstract: With image processing algorithms and in particular with deep learning being so powerful, it is tempting to concentrate on this processing side and less on the actual hardware taking the images. Lens selection is very often left to last in both R&D and product manufacturing cycles. Putting effort into selecting the right lens, will not only allow an engineer to leverage the full potential of a camera's image sensor but it is also one of the first tools of data reduction and system simplification, key points to building any solution. Familiarity with the following five key criteria will help select the best lens for any application.